REVITALISASI PENDIDIKAN ISLAM DI ERA DISRUPSI: STUDI TERHADAP PEMIKIRAN IBNU KHALDUN - Efendi, Rahmi Maldini; Dewi, Eva; Sutarmo (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This research examines the urgency and relevance of revitalizing Islamic education in the era of disruption, through a study of Ibn Khaldun's thought. The purpose of this study is to explore the relevance of Ibn Khaldun's ideas on educational components such as educators, students, curriculum and educational materials, as well as educational methods in facing the challenges of the times in the era of disruption marked by technological advances, globalization, and shifting values. This research uses the literature study method by analyzing various sources of literature, including books of interpretation, scientific journals, and reference books, to broaden insights. The results show that Ibn Khaldun's thought is very relevant to be used as a reference in building an adaptive and responsive Islamic education system. Ideas such as the strategic role of teachers, students as active subjects, integrative curriculum between naqliyah and aqliyah sciences, as well as applicable and contextual learning methods, offer concrete solutions to today's educational challenges. This research contributes to the development of Islamic education that is more relevant to contemporary challenges, and emphasizes the importance of reviving Islamic intellectual heritage for the future of the ummah. Keywords: Ibn Khaldun, Islamic Education, Revitalization, Disruption Era.